MultiSkipGraph: A Self-stabilizing Overlay Network that Maintains Monotonic Searchability - Luo, Linghui; Scheideler, Christian; Strothmann, Thim Frederik (Proceedings of the 2019 IEEE 33rd International Parallel and Distributed Processing Symposium (IPDPS '19))
Self-stabilizing overlay networks have the advantage of being able to recover from illegal states and faults. However, the majority of these networks cannot give any guarantees on their functionality while the recovery process is going on. We are especially interested in searchability, i.e., the functionality that search messages for a specific node are answered successfully if a node exists in the network. In this paper we investigate overlay networks that ensure the maintenance of monotonic searchability while the self-stabilization is going on. More precisely, once a search message from node u to another node v is successfully delivered, all future search messages from u to v succeed as well. We extend the existing research by focusing on skip graphs and present a solution for two scenarios: (i) the goal topology is a super graph of the perfect skip graph and (ii) the goal topology is exactly the perfect skip graph.

Debiasing Vandalism Detection Models at Wikidata - Heindorf, Stefan; Scholten, Yan; Engels, Gregor; Potthast, Martin (WWW)

A Digital Twin-Based Multi-Modal UI Adaptation Framework for Assistance Systems in Industry 4.0 - Josifovska, Klementina; Yigitbas, Enes; Engels, Gregor (Proceedings of the 21st International Conference on Human-Computer Interaction (HCII 2019))

Reference Framework for Digital Twins within Cyber-Physical Systems - Josifovska, Klementina; Yigitbas, Enes; Engels, Gregor (Proceedings of 5th International Workshop on Software Engineering for Smart Cyber-Physical Systems (SEsCPS'19))

Förderung von Kreativität in studentischen Kleingruppenprojekten in der Informatik – Ein Prototyping-basierter Ansatz - Strothmann, Thim Frederik (die hochschullehre)
Dieser Artikel erörtert, ob in studentischen Kleingruppenprojekten in der Informatik Kreativität und die Erarbeitung kreativer Ideen explizit gefördert werden kann. Dazu wird ein Seminarkonzept detailliert vorgestellt, welches auf zwei Grundkonzepten der Informatikpraxis beruht: agiles Projektvorgehen und Prototyping. Die Teilnehmenden des Seminars wurden gezielt in einen Kreativitätsprozess geleitet, indem sie für gegebene moderne Technologien (Virtual Reality, Augmented Reality, Drohnen, etc.) neuartige Nutzungsszenarien entwickeln sollten. Um zu evaluieren, ob das Lehrkonzept erfolgreich ist, wird sowohl die produktbezogene als auch die prozessbezogene Kreativität betrachtet. Für die produktbezogene Kreativität werden die von den Teilnehmenden erstellten Projektideen inklusive der benutzten Prototypingtechnik vorgestellt und bewertet. Die Teilnehmenden haben nicht nur eine enorme Breite an Ideen entwickelt (in der Summe ca. 40 bei 16 Teilnehmenden), sondern insbesondere auch acht Ideen im Verlaufe des Seminars sehr konkret weiterentwickelt. Hinsichtlich der prozessbezogenen Kreativität wird das Lehrkonzept durch mehrere Fragebögen eruiert. Die Studierenden sind mit dem Seminar, der Herangehensweise und den Ergebnissen sehr zufrieden, was unter anderem durch die äußerst positive studentische Veranstaltungskritik (u.a. 1,0 für den Gesamteindruck sowie Atmosphäre in der Veranstaltung) und die Auswertung der Evaluationsfragebögen unterstrichen wird. Auch von externen Beobachtern werden die erarbeiteten Ergebnisse und der Einsatz von Prototyping als sehr positiv bewertet.

WindCORES - Digital Transformation with Renewable Energy - Yigitbas, Enes; Schomaker, Gunnar (International Tube Association (ITAtube) Journal)

Detection and Resolution of Data-Flow Differences in Business Process Models - Jovanovikj, Ivan; Yigitbas, Enes; Gerth, Christian; Sauer, Stefan; Engels, Gregor (Information Systems Engineering in Responsible Information Systems - CAiSE Forum 2019, Rome, Italy, June 3-7, 2019, Proceedings)

Modular Construction of Context-Specific Test Case Migration Methods - Jovanovikj, Ivan; Yigitbas, Enes; Grieger, Marvin; Sauer, Stefan; Engels, Gregor (Proceedings of the 7th International Conference on Model-Driven Engineering and Software Development - Volume 1: MODELSWARD,)

Consistent Runtime Adaptation of User Interfaces - Anjorin, Anthony; Yigitbas, Enes; Kaindl, Hermann (Proceedings of the 8th International Workshop on Bidirectional Transformations (Bx 2019))

Towards Model-based Development of Context-aware Augmented Reality Applications - Yigitbas, Enes; Jovanovikj, Ivan; Sauer, Stefan; Engels, Gregor (Softwaretechnik-Trends, Proceedings of the 21st Workshop Software-Reengineering & Evolution (WSRE) & 10th Workshop Design for Future (DFF))

Context- and Data-driven Satisfaction Analysis of User Interface Adaptations Based on Instant User Feedback - Yigitbas, Enes; Hottung, André; Mansfield Rojas, Sebastian; Anjorin, Anthony; Sauer, Stefan; Engels, Gregor (Proceedings of the ACM on Human-Computer Interaction)

On-the-fly Usability Evaluation of Mobile Adaptive UIs through Instant User Feedback - Yigitbas, Enes; Jovanovikj, Ivan; Josifovska, Klementina; Sauer, Stefan; Engels, Gregor (Proceedings of the 17th IFIP TC.13 International Conference on Human-Computer Interaction (INTERACT 2019))

A Value-Centered Approach for Unique and Novel Software Applications - Senft, Björn; Rittmeier, Florian; Fischer, Holger Gerhard; Oberthür, Simon (Design, User Experience, and Usability. Practice and Case Studies)

A Context-aware Virtual Reality First Aid Training Application - Yigitbas, Enes; Heindörfer, Joshua; Engels, Gregor (Proceedings of the Mensch und Computer 2019 (MuC ’19))

A Model-based Framework for Context-aware Augmented Reality Applications - Yigitbas, Enes; Jovanovikj, Ivan; Sauer, Stefan; Engels, Gregor (Handling Security, Usability, User Experience and Reliability in User-Centered Development Processes (IFIP WG 13.2 & WG 13.5 International Workshop @ INTERACT2019))

ABIS 2019 – 23rd International Workshop on Personalization and Recommendation on the Web and Beyond - Augstein, Mirjam; Herder, Eelco; Wörndl, Wolfgang; Yigitbas, Enes (30th ACM Conference on Hypertext and Social Media (HT ’19), September 17–20, 2019, Hof, Germany)

Vandalism Detection in Crowdsourced Knowledge Bases - Heindorf, Stefan

Model-Driven Engineering of Self-Adaptive User Interfaces - Yigitbas, Enes

Debiasing Vandalism Detection Models at Wikidata (Extended Abstract) - Heindorf, Stefan; Scholten, Yan; Engels, Gregor; Potthast, Martin (INFORMATIK)

Projektmanagement und Vorgehensmodelle 2019. Neue Vorgehensmodelle in Projekten – Führung, Kulturen und Infrastrukturen im Wandel.

Partizipation von Beschäftigten in der Gestaltung einer digitalisierten Arbeitswelt 4.0 mittels einer Canvas-Methode - Fischer, Holger Gerhard; Rittmeier, Florian; Strothmann, Thim Frederik; Schwenniger, Nina (Arbeit 4.0 im Mittelstand)
Sinnvolle und gebrauchstaugliche digitale Assistenzsysteme, die Beschäftigte bei ihren alltäglichen Aufgaben unterstützen, stellen eine Herausforderung für viele Organisationen hinsichtlich der individuellen und organisationalen Akzeptanz einschließlich der Gebrauchstauglichkeit (Usability), dem Benutzererlebnis (User Experience, UX) und „Arbeit 4.0“-Aspekten dar. Vorhandene Methoden des Software Engineering sind nicht geeignet, Beschäftigte angemessen in die Gestaltung und Entwicklung zu integrieren und Lösungskonzepte solcher Systeme auf Augenhöhe zu betrachten. In diesem Beitrag wird eine leichtgewichtige Canvas-Methode vorgestellt, die sich mit diesen Herausforderungen befasst. Sie umfasst die menschliche, die geschäftliche sowie die technologische Perspektive in einem gemeinsamen Kommunikationsinstrument, dem „Digital Assistance System Canvas“. Erste Evaluationen zeigen, dass die Teilnehmenden das Canvas-Konzept schätzen und die Methode vielseitig in verschiedenen Szenarien einsetzbar ist. Vielfältige Fragen in den Canvas-Bausteinen bereichern die gemeinsame Diskussion über neue Systeme und die Verbesserung bzw. Sicherstellung der Akzeptanz sowie die Denkweise in frühen Phasen des Design- und Entwicklungsprozesses.

A feature-based classification of triple graph grammar variants - Weidmann, Nils; Oppermann, Robin; Robrecht, Patrick (Proceedings of the 12th ACM SIGPLAN International Conference on Software Language Engineering - SLE 2019)

Consistency management via a combination of triple graph grammars and linear programming - Weidmann, Nils; Anjorin, Anthony; Leblebici, Erhan; Schürr, Andy (Proceedings of the 12th ACM SIGPLAN International Conference on Software Language Engineering - SLE 2019)

Verteiltes Warenwirtschaftssystem [Distributed Warehouse System] - Göllner, Thomas; Schwarz, Jan-Hendrik; Gottschalk, Sebastian; Sauer, Stefan
Beschrieben ist ein verteiltes Warenwirtschaftssystem, bei dem der Kunde, Händler, und der Hersteller vernetzt sind. Dies wird bewerkstelligt durch einen Cloud-Speicher (105), der Cloud-Speicher (105) aufweisend ein Mittel zum Speichern (105a) von Daten, ein Mittel zum Empfangen von ersten Daten von einem ersten Netzwerkteilnehmer (110), wobei die ersten Daten zugehörig sind zu einem physischen Objekt, ein Mittel zum Empfangen von Anfragedaten von einem zweiten Netzwerkteilnehmer (120), ein Mittel zum Empfangen von zweiten Daten von einem dritten Netzwerkteilnehmer (130), wobei die zweiten Daten zugehörig sind zu den ersten Daten und zumindest ein Datum aufweisen, welches angepasst ist, die ersten Daten zu ändern in Abhängigkeit der empfangenen Anfragedaten, ein Mittel zum Ändern der ersten Daten basierend zumindest im Teil auf den zweiten Daten und den Anfragedaten und ein Mittel zum Senden eines geänderten Teils der ersten Daten von dem Cloud-Speicher (105) an den ersten Netzwerkteilnehmer (110).

Intertwined Development of Business Model and Product Functions for Mobile Applications: A Twin Peak Feature Modeling Approach - Gottschalk, Sebastian; Rittmeier, Florian; Engels, Gregor (Software Business)
Mobile app stores like Apple's AppStore or Google's PlayStore are highly competitive markets for third-party developers wanting to develop successful applications. During the development process, many developers focus on the multitude of product functions but neglect the business model as an equally important part. As a result, developers often fail to meet customer needs, leading to unnecessary development costs and poor market penetration. This, in turn, raises the question of how we intertwine the business model and product functions during the development process to ensure a better alignment between the two. In this paper, we show this intertwined development by adapting the concept of Twin Peaks to the business model and product functions. Based on feature modeling as an abstraction layer, we introduce the concept of a Business Model Decision Line (BMDL) to structure the business model decisions and their relation to product functions structured in a Software Product Line (SPL). The basis of our feature models is the analysis of top listed applications in the app stores of Apple and Google. To create and modify both models, we provide an incremental feature structuring and iterative feature selection process. This combination of abstraction layer and development process supports third-party developers to build successful applications both from a business and a product perspective.
Keywords: Intertwined Development; Twin Peaks; Feature Model; Business Model; Product Functions

From Pattern Invocation Networks to Rule Preconditions - Weidmann, Nils; Anjorin, Anthony; Stolte, Florian; Kraus, Florian (Proceedings of the 12th International Conference on Graph Transformation, ICGT 2019, Held as Part of STAF 2019)

Incremental (Unidirectional) Model Transformation with eMoflon::IBeX - Weidmann, Nils; Anjorin, Anthony; Robrecht, Patrick; Varró, Gergely (Proceedings of the 12th International Conference on Graph Transformation, ICGT 2019, Held as Part of STAF 2019)

Incremental Bidirectional Model Transformation with eMoflon::IBeX - Weidmann, Nils; Anjorin, Anthony; Fritsche, Lars; Varró, Gergely; Schürr, Andy; Leblebici, Erhan (Proceedings of the 8th International Workshop on Bidirectional Transformations co-located with the Philadelphia Logic Week, Bx@PLW 2019)

Specifying Web Interfaces for Command-line Applications Based on OpenAPI - Wolters, Dennis; Kirchhoff, Jonas; Engels, Gregor (Service-Oriented Computing – ICSOC 2019 Workshops)

Conception of a digital Sales Bonus System based on Blockchain Technology - N., N.

Design Options of Store-Oriented Software Ecosystems: An Investigation of Business Decisions - Jazayeri, Bahar; Zimmermann, Olaf; Engels, Gregor; Küster, Jochen; Kundisch, Dennis; Szopinski, Daniel (Proceeding of International Symposium on Business Modeling and Software Design)
Nowadays companies like Apple create ecosystems of third- party providers and users around their software platforms. Often online stores like Apple App Store are created to directly market third-party solutions. We call such ecosystems store-oriented software ecosystems. While the architecture of these ecosystems is mainly derived from busi- ness decisions of their owners, ecosystems with greatly different archi- tectural designs have been created. This diversity makes it challenging for future ecosystem providers to understand which architectural design is suitable to fulfill certain business decisions. In turn, opening a plat- form becomes risky while endangering intellectual property or scarifying quality of services. In this paper, we identify three main design options of store-oriented software ecosystems by classifying existing ecosystems based on similarities in their business decisions. We elaborate on the design options, discuss their main contributions, and provide exemplary ecosystems. Our work provides aspiring ecosystem providers with the reusable knowledge of existing ecosystems and helps them to take more informed architectural decisions and reduce risks in future.

Self-Stabilizing Supervised Publish-Subscribe Systems - Feldmann, Michael; Kolb, Christina; Scheideler, Christian; Strothmann, Thim Frederik (Proceedings of the 32nd IEEE International Parallel & Distributed Processing Symposium (IPDPS))
In this paper we present two major results: First, we introduce the first self-stabilizing version of a supervised overlay network (as introduced in~\cite{DBLP:conf/ispan/KothapalliS05}) by presenting a self-stabilizing supervised skip ring. Secondly, we show how to use the self-stabilizing supervised skip ring to construct an efficient self-stabilizing publish-subscribe system. That is, in addition to stabilizing the overlay network, every subscriber of a topic will eventually know all of the publications that have been issued so far for that topic. The communication work needed to processes a subscribe or unsubscribe operation is just a constant in a legitimate state, and the communication work of checking whether the system is still in a legitimate state is just a constant on expectation for the supervisor as well as any process in the system.
Keywords: Topological Self-stabilization; Supervised Overlay; Publish-Subscribe System

IoT-ASAP 2018: Message from the Chairs - Spalazzese, Romina; Platenius, Marie C.; Becker, Steffen; Engels, Gregor (2018 IEEE International Conference on Software Architecture Companion (ICSA-C))

Poster: CrossEcore: An Extendible Framework to Use Ecore and OCL across Platforms - Schwichtenberg, Simon; Jovanovikj, Ivan; Gerth, Christian; Engels, Gregor (Proceedings of the 40th International Conference on Software Engineering, ICSE 2018 - Companion Volume)
Today, model-driven approaches are a cornerstone in modern software development. The Eclipse Modeling Framework (EMF) is highly adopted in practice and generates Java code from platform-independent models with embedded Object Constraint Language (OCL) expressions. However, applications that target multiple platforms like Android, iOS, Windows, web browsers usually need to be implemented in different programming languages. Feature-complete Ecore and OCL runtime APIs are not available for all these platforms, such that their functionality has to be re-implemented. In this paper, we present CrossEcore: A multi-platform enabled modeling framework that generates C#, Swift, TypeScript, and JavaScript code from Ecore models with embedded OCL. An OCL compiler translates OCL expressions into expressions of the target language. The Ecore and OCL API can be consistently used across platforms, which facilitates application portability. CrossEcore is also extendible and can be easily adopted for new programming languages.

On the runtime of universal coating for programmable matter - J. Daymude, Joshua; Derakhshandeh, Zahra; Gmyr, Robert; Porter, Alexandra; W. Richa, Andrea; Scheideler, Christian; Strothmann, Thim Frederik (Natural Computing)

Digitalisierungspotenziale in Geschäftsprozessen effizient und effektiv erkennen (Effective and Efficient Identification of Digitalization Potentials in Business Processes) - Rittmeier, Florian; Engels, Gregor; Teetz, Alexander (Joint Proceedings of the Workshops at Modellierung 2018 co-located with Modellierung 2018, Braunschweig, Germany, February 21, 2018.)
Ein wichtiges Element der Digitalen Transformation ist die Digitalisierung der Prozesse in Unternehmen. Eine Herausforderung besteht hierbei in der systematischen Erkennung von Digitalisierungspotenzialen in Prozessen. Bestehende Ansätze benötigen Experten, welche Potenziale über ihre Erfahrung oder zeitaufwendig mithilfe von Musterkatalogen identifizieren. In diesem Artikel werden verschiedene Digitalisierungspotenziale klassifiziert und Muster für ein zukünftiges musterbasiertes Analyseverfahren zur automatisierten Identifikation von Digitalisierungspotenzialen in BPMN-Diagrammen beschrieben. Im Vergleich zu bestehenden Ansätzen erlaubt es Experten die Identifizierung von Digitalisierungspotenzialen effizienter und effektiver durchzuführen.
Keywords: Digitalisierungspotenziale; BPI; Digitale Transformation; Information Flow-Modellierung; Patterns; Requirements Engineering

Description Languages for Consistency Management Scenarios Based on Examples from the Industry Automation Domain - Anjorin, Anthony; Yigitbas, Enes; Leblebici, Erhan; Schürr, Andy; Lauder, Marius; Witte, Martin (Programming Journal)

Test Case Migration: A Reference Process Model and its Instantiation in an Industrial Context - Jovanovikj, Ivan; Yigitbas, Enes; Sauer, Stefan (Joint Proceedings of the Workshops at Modellierung 2018 co-located with Modellierung 2018, Braunschweig, Germany, February 21, 2018.)

Bidirectional Method Patterns for Language Editor Migration - Yigitbas, Enes; Anjorin, Anthony; Leblebici, Erhan; Grieger, Marvin (Modelling Foundations and Applications - 14th European Conference, ECMFA 2018, Held as Part of STAF 2018, Toulouse, France, June 26-28, 2018, Proceedings)

On the development of consistent user interfaces (extended abstract) - Anjorin, Anthony; Yigitbas, Enes; Kaindl, Hermann; Popp, Roman (Conference Companion of the 2nd International Conference on Art, Science, and Engineering of Programming, Nice, France, April 09-12, 2018)

Who Guards the Guards? On the Validation of Test Case Migration - Jovanovikj, Ivan; Yigitbas, Enes; Anjorin, Anthony; Sauer, Stefan (Softwaretechnik-Trends, Proceedings of the 20th Workshop Software-Reengineering & Evolution (WSRE) & 9th Workshop Design for Future (DFF))

Model-based UI Modernization: From Legacy UIs to Self-adaptive UIs - Jovanovikj, Ivan; Yigitbas, Enes; Sauer, Stefan (Softwaretechnik-Trends, Proceedings of the 20th Workshop Software-Reengineering & Evolution (WSRE) & 9th Workshop Design for Future (DFF))

Forming Tile Shapes with Simple Robots - Gmyr, Robert; Hinnenthal, Kristian; Kostitsyna, Irina; Kuhn, Fabian; Rudolph, Dorian; Scheideler, Christian; Strothmann, Thim Frederik (Proceedings of the 24th International Conference on DNA Computing and Molecular Programming)

Adapt Cases 4 BPM - A Modeling Framework for Process Flexibility in IIoT - Engels, Gregor; Strothmann, Thim Frederik; Teetz, Alexander (2018 IEEE 22nd International Enterprise Distributed Object Computing Workshop (EDOCW))

Tolerant consistency management in model-driven engineering - Weidmann, Nils (Proceedings of the 21st ACM/IEEE International Conference on Model Driven Engineering Languages and Systems Companion Proceedings - MODELS '18)

Real-time Graph-Based 3D Reconstruction of Sparse Feature Environments for Mobile Robot Applications - Gaspers, Daniel; Knorr, Christoph; Nickchen, Tobias; Nickchen, Daniel; Mertsching, Barbel; Mohamed, Mahmoud A. (2018 IEEE International Symposium on Safety, Security, and Rescue Robotics (SSRR))

Usability Evaluation of Model-Driven Cross-Device Web User Interfaces - Yigitbas, Enes; Anjorin, Anthony; Jovanovikj, Ivan; Kern, Thomas; Sauer, Stefan; Engels, Gregor (Proceedings of the 7th International Working Conference on Human-Centered Software Engineering (HCSE'18))

Forschendes Lernen in der Informatik - In praxisnaher Projektgruppe einen Softwareentwicklungsprozess erforschen - Senft, Björn; Oberthür, Simon; Fischer, Holger Gerhard (Schriften zur allgemeinen Hochschuldidaktik - Band 3. Tagungsband Forschendes Lernen - The wider view)

Assist Users to Straightaway Suggest and Describe Experienced Problems - Senft, Björn; Fischer, Holger Gerhard; Oberthür, Simon; Patkar, Nitish (Design, User Experience, and Usability: Theory and Practice)

A Canvas Method to Foster Interdisciplinary Discussions on Digital Assistance Systems - Fischer, Holger Gerhard; Senft, Björn; Rittmeier, Florian; Sauer, Stefan (Design, User Experience, and Usability: Theory and Practice. Proceedings of the 20th International Conference on Human-Computer Interaktion (HCI International 2018))

Presentation: Who Guards the Guards? On the Validation of Test Case Migration - Jovanovikj, Ivan; Güldali, Baris

Patterns of Store-oriented Software Ecosystems: Detection, Classification, and Analysis of Design Options - Jazayeri, Bahar; Zimmermann, Olaf; Küster, Jochen; Engels, Gregor; Kundisch, Dennis; Szopinski, Daniel (The Latin American Conference on Pattern Languages of Programs (SLPLoP))
Software companies nowadays create ecosystems of users and third-party providers around their platforms. They often provide online stores so that the third-party developments can be exposed to users directly. The resulting ecosystems differ significantly from each other in their architectural designs because their providers differ in terms of business goals and contexts. Until now, this architectural diversity and rationale behind it are not well-understood. Therefore, it is not clear which software features contribute to ecosystem’s success with respect to certain business goals and context. This hinders systematic creation of ecosystems in the future. Thus, decision-making becomes too risky; for future ecosystem providers, which may lead to creation of inefficient ecosystems that lack critical features, and for third-party providers to rely on ad-hoc choices while deciding on suitability of an ecosystem for their future career. In this paper, we introduce three design patterns for store- oriented software ecosystems by classifying the design decisions, business goals, and context of 111 store-oriented software ecosystems. Each design pattern provides an architectural solution to achieve a different business goal while supporting a different context. We discuss how the design patterns are applied together in order to achieve more business goals. Our work supports ecosystem and third-party providers by sharing practice-proven architectural solutions, helping them to take informed architectural decisions and reduce technical risks.

Einsatz von Classroom-Response-Systemen und Peer Instruction in der Veranstaltung Grundlagen von Datenbanken - Wolters, Dennis (die hochschullehre)

Context-specific Quality Evaluation of Test Cases - Jovanovikj, Ivan; Narasimhan, Vishwak; Engels, Gregor; Sauer, Stefan (Proceedings of the 6th International Conference on Model-Driven Engineering and Software Development - Volume 1: MODELSWARD,)

Model-Driven Test Case Migration: The Test Case Reengineering Horseshoe Model - Jovanovikj, Ivan; Engels, Gregor; Anjorin, Anthony; Sauer, Stefan (Information Systems in the Big Data Era - CAiSE Forum 2018, Tallinn, Estonia, June 11-15, 2018, ProceedingIs)
Existing test cases represent important assets, which are worth reusing in software migration projects. The benefit is twofold, reuse of relevant information as well cost saving by avoiding design of new test cases. As test cases are implemented in the same or a compatible technology as the system they are testing, they have to somehow follow the system migration, i.e., they should be co-migrated. Due to the size of the test case set, and often missing conformity in the structure of the test cases, migration of test cases is a quite challenging task. As model-driven engineering has been established to manage those complex tasks, we apply it in the test case domain. In this paper, we propose a generic migration method based on model-driven reengineering techniques. Our method which involves reverse engineering, restructuring, and forward engineering is applied in an industrial case study where appropriate tooling was developed as well.

Model-integrating development of software systems: a flexible component-based approach - Derakhshanmanesh, Mahdi; Ebert, Jürgen; Grieger, Marvin; Engels, Gregor (Software & Systems Modeling)

2018 IEEE Symposium on Visual Languages and Human-Centric Computing (VL/HCC) - Cunha, Jácome; Fernandes, Joao Paulo; Kelleher, Caitlin; Mendes, Jorge; Engels, Gregor (Proceedings of 2018 IEEE Symposium on Visual Languages and Human-Centric Computing (VL/HCC), Lisbon, Portugal, October 1-4, 2018)

Gerechtigkeit in flexiblen Arbeits- und Managementprozessen - Engels, Gregor; Maier, Günter W.; Ötting, Sonja K.; Steffen, Eckhard; Teetz, Alexander (Zukunft der Arbeit – Eine praxisnahe Betrachtung)

Semantic Data Mediator: Linking Services to Websites - Wolters, Dennis; Heindorf, Stefan; Kirchhoff, Jonas; Engels, Gregor (Service-Oriented Computing -- ICSOC 2017 Workshops)
Many websites offer links to social media sites for convenient content sharing. Unfortunately, those sharing capabilities are quite restricted and it is seldom possible to share content with other services, like those provided by a user's favorite applications or smart devices. In this paper, we present Semantic Data Mediator (SDM) --- a flexible middleware linking a vast number of services to millions of websites. Based on reusable repositories of service descriptions defined by the crowd, users can easily fill a personal registry with their favorite services, which can then be linked to websites by SDM. For this, SDM leverages semantic data, which is already available on millions of websites due to search engine optimization. Further support for our approach from website or service developers is not required. To enable the use of a broad range of services, data conversion services are automatically composed by SDM to transform data according to the needs of the different services. In addition to linking web services, various service adapters allow services of applications and smart devices to be linked as well. We have fully implemented our approach and present a real-world case study demonstrating its feasibility and usefulness.

Business Process Management - 15th International Conference, BPM 2017, Barcelona, Spain, September 10-15, 2017, Proceedings Lecture Notes in Computer Science

Business Process Management Forum - BPM Forum 2017, Barcelona, Spain, September 10 - 15, 2017, Proceedings Lecture Notes in Business Information Processing 297

Message from the IoT-ASAP Chairs

Mensch und Computer 2017 - Usability Professionals. Tagungsband

Towards systematic spreadsheet construction processes - Mendes, Jorge; Cunha, Jacome; Duarte, Francisco; Engels, Gregor; Saraiva, Joao; Sauer, Stefan (2017 IEEE/ACM 39th International Conference on Software Engineering Companion (ICSE-C))

On-The-Fly Computing Meets IoT Markets - Towards a Reference Architecture - Jazayeri, Bahar; Schwichtenberg, Simon (Proceedings of the International Conference on Software Architecture (ICSA) IoT-ASAP Workshop)
The Internet of Things (IoT) connects the things of our everyday life and supports usin our common activities.Several markets for IoT services have been created. These markets enable IoT users to search and compose services in order to support an IoT activity.However, existing IoT markets like IFTTT (If This Then That) are not convenient for users with respect to service discovery and composition.The objective of On-the-fly (OTF) computing is to configure and provide software markets that fulfill individual users' wishes by the automatic on-the-fly composition of single services.The architecture framework of On-the-fly computing markets helps architects to systematically develop these systems in different domains.In this paper, we use our OTF architectural framework to examine the requirements of a reference architecture for IoT markets.Furthermore, we perform a comparison between the architecture of IFTTT as an existing IoT market with this reference architecture. The results show how existing IoT markets can be improved. In return, the practical knowledge of IFTTT is taken to the reference architecture.This knowledge helps to overcome the limitations of today's IoT markets or creating new markets in the future.

Concept-Based Engineering of Situation-Specific Migration Methods - Grieger, Marvin; Fazal-Baqaie, Masud; Engels, Gregor; Klenke, Markus (Software Engineering 2017)

Systematic spreadsheet construction processes - Mendes, Jorge; Cunha, Jácome; Duarte, Francisco; Engels, Gregor; Saraiva, Joao; Sauer, Stefan (Proceedings of the 39th International Conference on Software Engineering, ICSE 2017, Buenos Aires, Argentina, May 20-28, 2017 - Companion Volume)

On the Necessity of an Architecture Framework for On-The-Fly Computing - Jazayeri, Bahar; Schwichtenberg, Simon (Proceedings of Softwaretechnik-Trends Workshops)

Adapt-UI: an IDE supporting model-driven development of self-adaptive UIs - Yigitbas, Enes; Sauer, Stefan; Engels, Gregor (Proceedings of the ACM SIGCHI Symposium on Engineering Interactive Computing Systems, EICS 2017, Lisbon, Portugal, June 26-29, 2017)

Model-Driven Context Management for Self-adaptive User Interfaces - Yigitbas, Enes; Grün, Silas; Sauer, Stefan; Engels, Gregor (Ubiquitous Computing and Ambient Intelligence - 11th International Conference, UCAmI 2017, Philadelphia, PA, USA, November 7-10, 2017, Proceedings)

XDAI-A: Framework for Enabling Cross-Device Integration of Android Apps - Wolters, Dennis; Kirchhoff, Jonas; Gerth, Christian; Engels, Gregor (Service-Oriented Computing -- ICSOC 2016 Workshops)
A lot of people are managing multiple computing devices suited for different purposes, like private and work devices. Integrating applications running on different devices is often a problem, because the services provided by those applications are not meant to be integrated. In this demonstration, we present our XDAI-A framework which enables cross-device integration of services provided by Android apps. The framework uses adapters to convert Android-internal service interfaces of existing apps into external services with a platform-independent interface that can be accessed from applications on other devices and even other platforms. Our ready-to-use framework does not require to alter existing Android apps, since the adapters are installed separately. For the convenient specification of adapters, our framework comes with a domain-specific language (DSL). Additionally, we provide an infrastructure to find and integrate devices and their applications' services.

A Human-Centered Perspective on Software Quality: Acceptance Criteria for Work 4.0 - Fischer, Holger Gerhard; Engler, Michael; Sauer, Stefan (Design, User Experience, and Usability: Theory, Methodology, and Management)

Akzeptierte Assistenzsysteme in der Arbeitswelt 4.0 durch systematisches Human-Centered Software Engineering - Fischer, Holger Gerhard; Senft, Björn; Stahl, Katharina (Wissenschafts- und Industrieforum 2017 - Intelligente Technische Systeme)

Mensch und Computer 2017 - Usability Professionals. Tagungsband

Deep Learning Assisted Heuristic Tree Search for the Container Pre-marshalling Problem - Hottung, André; Tanaka, Shunji; Tierney, Kevin (CoRR abs/1709.09972)

Towards DevOps in Multi-provider Projects - Fazal-Baqaie, Masud; Güldali, Baris; Oberthür, Simon (CSE@SE 2017)

Presentation: Framework for Constructing Context-Specific Migration Methods for Test Cases - Jovanovikj, Ivan

From User Demand to Software Service: Using Machine Learning to Automate the Requirements Specification Process - van Rooijen, Lorijn; Bäumer, Frederik Simon; Platenius, Marie Christin; Geierhos, Michaela; Hamann, Heiko; Engels, Gregor (2017 IEEE 25th International Requirements Engineering Conference Workshops (REW))
Bridging the gap between informal, imprecise, and vague user requirements descriptions and precise formalized specifications is the main task of requirements engineering. Techniques such as interviews or story telling are used when requirements engineers try to identify a user's needs. The requirements specification process is typically done in a dialogue between users, domain experts, and requirements engineers. In our research, we aim at automating the specification of requirements. The idea is to distinguish between untrained users and trained users, and to exploit domain knowledge learned from previous runs of our system. We let untrained users provide unstructured natural language descriptions, while we allow trained users to provide examples of behavioral descriptions. In both cases, our goal is to synthesize formal requirements models similar to statecharts. From requirements specification processes with trained users, behavioral ontologies are learned which are later used to support the requirements specification process for untrained users. Our research method is original in combining natural language processing and search-based techniques for the synthesis of requirements specifications. Our work is embedded in a larger project that aims at automating the whole software development and deployment process in envisioned future software service markets.
Keywords: Software; Unified modeling language; Requirements engineering; Ontologies; Search problems; Natural languages

WSDM Cup 2017: Vandalism Detection and Triple Scoring - Heindorf, Stefan; Potthast, Martin; Bast, Hannah; Buchhold, Björn; Haussmann, Elmar (WSDM)

A Characterization for Decidable Separability by Piecewise Testable Languages - Czerwinski, Wojciech; Martens, Wim; van Rooijen, Lorijn; Zeitoun, Marc; Zetzsche, Georg (Discrete Mathematics & Theoretical Computer Science)

Visual Requirements Modeling for Cross-Device Systems - Wolters, Dennis; Gerth, Christian; Engels, Gregor (Computer Science and Information Systems (ComSIS))

Towards a Framework for Constructing Context-Specific Migration Methods for Test Cases - Jovanovikj, Ivan; Sauer, Stefan (Softwaretechnik-Trends, Proceedings of the 19th Workshop Software-Reengineering & Evolution (WSRE) & 8th Workshop Design for Future (DFF))

Active Coevolutionary Learning of Requirements Specifications from Examples - Wever, Marcel Dominik; van Rooijen, Lorijn; Hamann, Heiko (Proceedings of the Genetic and Evolutionary Computation Conference (GECCO))
Within software engineering, requirements engineering starts from imprecise and vague user requirements descriptions and infers precise, formalized specifications. Techniques, such as interviewing by requirements engineers, are typically applied to identify the user’s needs. We want to partially automate even this first step of requirements elicitation by methods of evolutionary computation. The idea is to enable users to specify their desired software by listing examples of behavioral descriptions. Users initially specify two lists of operation sequences, one with desired behaviors and one with forbidden behaviors. Then, we search for the appropriate formal software specification in the form of a deterministic finite automaton. We solve this problem known as grammatical inference with an active coevolutionary approach following Bongard and Lipson [2]. The coevolutionary process alternates between two phases: (A) additional training data is actively proposed by an evolutionary process and the user is interactively asked to label it; (B) appropriate automata are then evolved to solve this extended grammatical inference problem. Our approach leverages multi-objective evolution in both phases and outperforms the state-of-the-art technique [2] for input alphabet sizes of three and more, which are relevant to our problem domain of requirements specification.

A Variability Model for Store-oriented Software Ecosystems: An Enterprise Perspective (Supplementary Material) - Jazayeri, Bahar; Zimmermann, Olaf; Engels, Gregor; Kundisch, Dennis

A Variability Model for Store-oriented Software Ecosystems: An Enterprise Perspective - Jazayeri, Bahar; Zimmermann, Olaf; Engels, Gregor; Kundisch, Dennis (Proceedings of the 15th International Conference on Service Oriented Computing (ICSOC))
Pioneers of today’s software industry like Salesforce and Apple have established successful ecosystems around their software platforms. Architectural knowledge of the existing ecosystems is implicit and fragmented among online documentation. In protection of intellectual property, existing documentation hardly reveals influential business strategies that affect the ecosystem structure. Thus, other platform providers can hardly learn from the existing ecosystems in order to systematically make reasonable design decisions with respect to their business strategies to create their own ecosystems. In this paper, we identify a variability model for architectural design decisions of a store-oriented software ecosystem product line from an enterprise perspective, comprising business, application, and infrastructure views. We derive the variability model from fragmentary material of existing ecosystems and a rigorous literature review using a research method based on the design science paradigm. To show its validity, we describe real-world ecosystems from diverse domains using the variability model. This knowledge helps platform providers to develop customized ecosystems or to recreate existing designs in a systematic way. This, in turn, contributes to an increase in designer and developer productivity.

Linking Services to Websites by Leveraging Semantic Data - Wolters, Dennis; Heindorf, Stefan; Kirchhoff, Jonas; Engels, Gregor (2017 IEEE International Conference on Web Services (ICWS))
Websites increasingly embed semantic data for search engine optimization. The most common ontology for semantic data, schema.org, is supported by all major search engines and describes over 500 data types, including calendar events, recipes, products, and TV shows. As of today, users wishing to pass this data to their favorite applications, e.g., their calendars, cookbooks, price comparison applications or even smart devices such as TV receivers, rely on cumbersome and error-prone workarounds such as reentering the data or a series of copy and paste operations. In this paper, we present Semantic Data Mediator (SDM), an approach that allows the easy transfer of semantic data to a multitude of services, ranging from web services to applications installed on different devices. SDM extracts semantic data from the currently displayed web page on the client-side, offers suitable services to the user, and by the press of a button, forwards this data to the desired service while doing all the necessary data conversion and service interface adaptation in between. To realize this, we built a reusable repository of service descriptions, data converters, and service adapters, which can be extended by the crowd. Our approach for linking services to websites relies solely on semantic data and does not require any additional support by either website or service developers. We have fully implemented our approach and present a real-world case study demonstrating its feasibility and usefulness.
Keywords: Services; Websites; Semantic Data; schema.org; Data Conversion; Interface Adaptation; Mediation

Overview of the Wikidata Vandalism Detection Task at WSDM Cup 2017 - Heindorf, Stefan; Potthast, Martin; Engels, Gregor; Stein, Benno (WSDM Cup 2017 Notebook Papers)
We report on the Wikidata vandalism detection task at the WSDM Cup 2017. The task received five submissions for which this paper describes their evaluation and a comparison to state of the art baselines. Unlike previous work, we recast Wikidata vandalism detection as an online learning problem, requiring participant software to predict vandalism in near real-time. The best-performing approach achieves a ROC-AUC of 0.947 at a PR-AUC of 0.458. In particular, this task was organized as a software submission task: to maximize reproducibility as well as to foster future research and development on this task, the participants were asked to submit their working software to the TIRA experimentation platform along with the source code for open source release.

Proceedings of the WSDM Cup 2017: Vandalism Detection and Triple Scoring - Potthast, Martin; Heindorf, Stefan; Bast, Hannah (arXiv:1712.09528)
The WSDM Cup 2017 was a data mining challenge held in conjunction with the 10th International Conference on Web Search and Data Mining (WSDM). It addressed key challenges of knowledge bases today: quality assurance and entity search. For quality assurance, we tackle the task of vandalism detection, based on a dataset of more than 82 million user-contributed revisions of the Wikidata knowledge base, all of which annotated with regard to whether or not they are vandalism. For entity search, we tackle the task of triple scoring, using a dataset that comprises relevance scores for triples from type-like relations including occupation and country of citizenship, based on about 10,000 human relevance judgements. For reproducibility sake, participants were asked to submit their software on TIRA, a cloud-based evaluation platform, and they were incentivized to share their approaches open source.

Features of IT Service Markets: A Systematic Literature Review (Supplementary Material) - Jazayeri, Bahar; Platenius, Marie Christin; Engels, Gregor; Kundisch, Dennis

Features of IT Service Markets: A Systematic Literature Review - Jazayeri, Bahar; Platenius, Marie; Engels, Gregor; Kundisch, Dennis (Proceedings of the 14th International Conference on Service Oriented Computing (ICSOC))
The provision of IT solutions over electronic marketplaces became prominent in recent years. We call such marketplaces IT service markets. IT service markets have some core architectural building blocks that impact the quality attributes of these markets. However, these building blocks and their impacts are not well-known. Thus, design choices for IT service markets have been made ad-hoc until now. Furthermore, only single aspects of such markets have been investigated until now, but a comprehensive view is missing.In this paper, we identify common features and their interrelations on the basis of a systematic literature review of 60 publications using grounded theory.This knowledge provides an empirical evidence on the interdisciplinary design choices of IT service markets and it serves as a basis to support market providers and developers to integrate market features. Thereby, we make a first step towards the creation of a reference model for IT service markets that provides a holistic integrated view that can be used to create and maintain successful markets in the future.

An Overview of Service Specification Language and Matching in On-The-Fly Computing (v0.3) - Platenius, Marie Christin; Josifovska, Klementina; van Rooijen, Lorijn; Arifulina, Svetlana; Becker, Matthias; Engels, Gregor; Schäfer, Wilhelm

Automatized Derivation of Comprehensive Specifications for Black-box Services - Schwichtenberg, Simon (Proceedings of the 38th International Conference on Software Engineering Companion (ICSE))
Today, cloud vendors host third party black-box services, whose developers usually provide only textual descriptions or purely syntactical interface specifications. Cloud vendors that give substantial support to other third party developers to integrate hosted services into new software solutions would have a unique selling feature over their competitors. However, to reliably determine if a service is reusable, comprehensive service specifications are needed. Characteristic for comprehensive in contrast to syntactical specifications are the formalization of ontological and behavioral semantics, homogeneity according to a global ontology, and a service grounding that links the abstract service description and its technical realization. Homogeneous, semantical specifications enable to reliably identify reusable services, whereas the service grounding is needed for the technical service integration. In general, comprehensive specifications are not availableand have to be derived. Existing automatized approaches are restricted to certain characteristics of comprehensiveness. In my PhD, I consider an automatized approach to derive fully-fledged comprehensive specifications for black-box services. Ontological semantics are derived from syntactical interface specifications. Behavioral semantics are mined from call logs that cloud vendors create to monitor the hosted services. The specifications are harmonized over a global ontology. The service grounding is established using traceability information. The approach enables third party developers to compose services into complex systems and creates new sales channels for cloud and service providers.

Architectural Management of On-The-Fly Computing Markets - Jazayeri, Bahar (Proceedings of the 10th European Conference on Software Architecture (ECSA Workshops))
Existing software markets like Google Play allow users to search among available Apps and select one based on the description provided for the App or based on its rating. Future software markets facilitate on-the-fly composition of such Apps based on users’ individual wishes. Realizing such On-The-Fly Computing (OTF) markets requires support of sophisticated software features. In addition, suitable orchestration among such features needs to ensure well-alignment of business and IT aspects in case of run-time changes like market dynamics. However, all these introduce new architectural and management complexities, which are specific to such markets. An architecture framework for OTF markets will include design solutions to overcome these complexities. In my PhD, I aim at identifying an architecture framework for OTF markets including main architectural building blocks and a systematic development process. Such an architecture framework enables the development of OTF markets in the future. Furthermore, this knowledge can be used as a basis to improve existing software markets by integrating missing functionalities.

Mensch und Computer 2016 - Usability Professionals. Tagungsband

SOFSEM 2016: Theory and Practice of Computer Science

Theory and Practice of Model Transformations - 9th International Conference ICMT 2016, Held as Part of STAF 2016, Vienna, Austria, July 4-5, 2016, Proceedings

SOFSEM 2016: Theory and Practice of Computer Science - Proceedings Volume II

Automated Quality Analysis of Software Engineering Method Models - Fazal-Baqaie, Masud; Kluthe, Frank (Proceedings of the 4th International Conference on Model-Driven Engineering and Software Development)

Ganzheitliches Qualitätsmanagement in agilen Groß- Projekten - Fazal-Baqaie, Masud; Güldali, Baris; Grieger, Marvin (Proceedings of Projektmanagement und Vorgehensmodelle 2016)

Concept-Based Engineering of Situation-Specific Migration Methods - Grieger, Marvin; Fazal-Baqaie, Masud; Engels, Gregor; Klenke, Markus (Proceedings of the 15th International Conference on Software Reuse (ICSR))